Peningkatkan Kualitas Santri melalui Sistem Pendidikan Pondok Pesantren Terpadu - Syaifi, Mat (Moderasi : Journal of Islamic Studies, 2023)
The quality of students is the main characteristic of a person, whether individual or group. To strengthen the quality of a student, there is a real need for an Integrated Islamic Boarding School Education system. The Integrated Islamic Boarding School Education System is classified as a democratic Islamic Boarding School type where the Islamic Boarding School system always holds deliberations with the entire board of teachers and staff in determining every decision that will be taken. Integrated Islamic Boarding Schools are classified as a democratic type of Islamic Boarding School where the Islamic Boarding School system always holds deliberations with the entire board of teachers and staff. In determining every decision to be taken. This research is a qualitative research. Research that describes data content, data quotations and provides an overview of report presentation through direct observation, interviews and documentary studies. The implementation of the integrated Islamic Boarding School education system at Darul Ulum in an effort to improve the quality of students is an Integrated Islamic Boarding School education system of the democratic Islamic Boarding School type where the Islamic Boarding School system always holds deliberations with the entire board of teachers and staff in determining every decision that will be taken. This integrated education system carries out its management role by not providing boundaries or differences between ustadz/ustadzah, staff and administration. They blend into one unit. By making efforts to apply the programs that have been planned and prepared by the integrated Islamic boarding school education system. Also evaluating the quality of student education programs which is carried out once a week.